Decision behaviour, analysis and support - French, Simon 1950- (Cambridge University Press, 2009)
Behavioural studies have shown that while humans may be the best decision makers on the planet, we are not quite as good as we think we are. We are regularly subject to biases, inconsistencies and irrationalities in our decision making. Decision Behaviour, Analysis and Support explores perspectives from many different disciplines to show how we can help decision makers to deliberate and make better decisions. It considers both the use of computers and databases to support decisions as well as human aids to building analyses and some fast and frugal tricks to aid more consistent decision making. In its exploration of decision support it draws together results and observations from decision theory, behavioural and psychological studies, artificial intelligence and information systems, philosophy, operational research and organisational studies. This provides a valuable resource for managers with decision-making responsibilities and students from a range of disciplines, including management, engineering and information systems
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Decision making; Entscheidungstheorie; Entscheidungsprozess